2023
DOI: 10.3390/cancers15051474
|View full text |Cite
|
Sign up to set email alerts
|

A Triphenylphosphonium-Functionalized Delivery System for an ATM Kinase Inhibitor That Ameliorates Doxorubicin Resistance in Breast Carcinoma Mammospheres

Abstract: The enzyme ataxia-telangiectasia mutated (ATM) kinase is a pluripotent signaling mediator which activates cellular responses to genotoxic and metabolic stress. It has been shown that ATM enables the growth of mammalian adenocarcinoma stem cells, and therefore the potential benefits in cancer chemotherapy of a number of ATM inhibitors, such as KU-55933 (KU), are currently being investigated. We assayed the effects of utilizing a triphenylphosphonium-functionalized nanocarrier delivery system for KU on breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In this regard, some well-designed nanocarriers can be used to effectively deliver SRC-3 inhibitors into rapidly proliferating cells, such as CSCs. Recent studies have shown that KU-55933, an ATM inhibitor [297], and chloroquine, a lysosome inhibitor [298], can be effectively delivered to breast CSCs using the triphenylphosphonium-functionalized hyperbranched polyethylenimine nanoparticles (PTPP) [299,300]. Similarly, PTPP or PTPPbased nanocarriers could be promising approaches to effectively deliver SRC-3 inhibitors to cells.…”
Section: Src-3 Is a Promising Target To Overcome Therapy Resistance I...mentioning
confidence: 99%
“…In this regard, some well-designed nanocarriers can be used to effectively deliver SRC-3 inhibitors into rapidly proliferating cells, such as CSCs. Recent studies have shown that KU-55933, an ATM inhibitor [297], and chloroquine, a lysosome inhibitor [298], can be effectively delivered to breast CSCs using the triphenylphosphonium-functionalized hyperbranched polyethylenimine nanoparticles (PTPP) [299,300]. Similarly, PTPP or PTPPbased nanocarriers could be promising approaches to effectively deliver SRC-3 inhibitors to cells.…”
Section: Src-3 Is a Promising Target To Overcome Therapy Resistance I...mentioning
confidence: 99%